Variabel-Variabel yang Berpengaruh Terhadap Keputusan Wisatawan untuk Membeli Makanan di Objek Wisata Religi Desa Giri - Siti Mundari; Herlina Herlina (Universitas Teuku Umar, 2022)
As the Covid-19 case decreases in Gresik Regency, tourism destination have begun to open, including the Sunan Giri Religious tourism. By the opening of these tourism destination, the opportunity for small and medium industry to resell their products is widely opened. To increase sales, especially food as souvenirs or consumed on the spot, it is necessary to do research to find out what factors influence consumer decisions in buying food. This study aims to determine the variables that influence the decision of tourists to buy food at the religious tourism object of Giri Village. The hypothesis that the consumer's decision to buy food (Y) is influenced by price, product, place of sale and promotion (X1, X2, X3, X4), and analyzed by Multiple Linear Regression. The method used to obtain information from respondents is in the form of a questionnaire. The instrument test was carried out to measure the validity and consistency of the questionnaire, the results were that all indicator variables were valid and reliable. The coefficient of determination in the multiple linear test is 0.864 which can be interpreted that the independent variables X1, X2, X3, and X4 have a contribution effect of 86.4% to the Y variable, and the other 13.6% is influenced by other factors outside the independent variables studied. . Simultaneous hypothesis testing with the F test resulted in the conclusion that the price, product, place of sale, and promotion variables together had a significant effect on purchasing decisions. While the promotion variable partially has no significant effect on purchasing decisions.